Ketersediaan Fasilitas Wisata terhadap Pengembangan Kawasan Wisata Taman Prasejarah Leang-leang - Zulkifli Rahman R P; Asmuliany Andi; Khairul Sani Usman (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2026)
The Leang-Leang Prehistoric Park is a cultural heritage tourism area with considerable archaeological and educational potential; however, its development is constrained by the limited quality of supporting tourism facilities. This study aims to analyze the availability and condition of tourism facilities as a basis for formulating development directions for the area. A mixed-method approach was applied by combining quantitative measurement using a Likert scale with qualitative descriptive analysis based on field observations, documentation, and limited interviews. Facility evaluation was conducted using five indicators: physical condition, functionality, cleanliness, comfort, and maintenance. The findings indicate that the tourism facility availability index reaches 60 percent, categorized as moderate. Facilities with the lowest scores include pedestrian pathways, worship facilities, gazebos, park benches, information centers, and souvenir shops, which negatively affect visitor comfort and experience quality. These results emphasize the need for targeted facility improvements through zoning arrangements, strengthening basic facilities, and implementing conservation-based tourism principles to support the sustainable development of the prehistoric tourism area.